Sentidos produzidos pelo sistema de recomendações na interface cultural da Netflix - Moraes, Jader Fontoura de (Universidade do Vale do Rio dos Sinos, 2021)
This research talks about the meanings produced by Recommending Systems on streaming platform Netflix’s cultural interfaces. Using Bergson’s intuition method (BERGSON, 2006; DELEUZE, 1999) to comprehend the Recommending Systems as a virtual that updates itself inside Netflix’s graphical user interfaces, or cultural interfaces (MANOVICH, 2001), which are filled with particular meanings in its language. This experiment was made through cartography and flânerie (BENJAMIN, 2009), with escavations made through technical documents and other information about the platform. In this experiment, Netflix’s cultural interface territory was mapped through screenshots taken through the navigation of three profiles which differientiate themselves by the usage of specific title research, multiple device usage and the avaliation system inside the platform. Experiments results were described through Benjamin’s constellations (BENJAMIN, 2009) related to criteria inferred by examining the Recommending System movements. The proposed constellations were: transparency meanings through age criteria, individuation meanings through regional criteria, niche meanings through categorization criteria and stickyness meanings through exclusivity criteria. We found out that there is an ambivalence on communications of users and of Netflix as a Corporation, which is evident through the cultural interface, where the users interests can bend to the first constellations described and corporate interests bend to the last ones.
Keywords: Sistemas de recomendação; Interfaces culturais; Constelações de sentido; Netflix; Streaming; Recommending systems; Cultural interfaces; Constellations; ACCNPQ::Ciências Sociais Aplicadas::Comunicação